Chlorination of 2-phenoxypropanoic acid with NCP in aqueous acetic acid - Segurado, Manuel A. P. (2015)
Rate constants were measured for the oxidative chlorodehydrogenation of (R,S)-2-phenoxypropanoic acid and nine ortho-, ten para- and five meta-substituted derivatives using (R,S)-1-chloro-3-methyl-2,6-diphenylpiperidin-4-one (NCP) as chlorinating agent. The kinetics was run in 50% (v/v) aqueous acetic acid acidified with perchloric acid under pseudo-first-order conditions with respect to NCP at temperature intervals of 5 K between 298 and 318 K, except at the highest temperature for the meta derivatives. The dependence of rate constants on temperature was analyzed in terms of the isokinetic relationship (IKR). For the 20 reactions studied at five different temperatures, the isokinetic temperature was estimated to be 382 K, which suggests the preferential involvement of water molecules in the rate-determining step. The dependence of rate constants on meta and para substitution was analyzed using the tetralinear extension of the Hammett equation. The parameter lambda for the para/meta ratio of polar substituent effects was estimated to be 0.926, and its electrostatic modeling suggests the formation of an activated complex bearing an electric charge near the oxygen atom belonging to the phenoxy group. A new approach is introduced for examining the effect of ortho substituents on reaction rates. Using IKR-determined values of activation enthalpies for a set of nine pairs of substrates with a given substituent, a linear correlation is found between activation enthalpies of ortho and para derivatives. The correlation is interpreted in terms of the selectivity of the reactant toward para- or ortho-monosubstituted substrates, the slope of which being related to the ortho effect. This slope is thought to be approximated by the ratio of polar substituent effects from ortho and para positions in benzene derivatives. Using the electrostatic theory of through-space interactions and a dipole length of 0.153 nm, this ratio was calculated at various positions of a charged reaction center along the benzene C-1-C-4 axis, being about 2.5 near the ring and decreasing steeply with increasing distance until reaching a minimum value of -0.565 at 1.3 nm beyond the aromatic ring. Activation enthalpies and entropies were estimated for substrates bearing the isoselective substituent in either ortho and para positions, being demonstrated that they are much different from the values for the parent substrate. The electrophilic attack on the phenolic oxygen atom by the protonated chlorinating agent is proposed as the rate-determining step, this step being followed by the fast rearrangement of the intermediate thus formed, leading to products containing chlorine in the aromatic ring.